O idoso e o lugar: o impacto biopsicossocial do fator espacial na terceira idade - OLIVEIRA, Raíssa Souza de (2022)
The increase of the elderly population in the world since the second half of the 20th century has become essential to better understand the biopsychosocial dimensions that influence aging. A factor that deserves to be highlighted in this context is the Space, which through the lived experience acquires a subjective dimension and becomes a place. Given this, the present study aims to identify the impacts that the spatial factor exercises on aging and on the mental health of the elderly. This investigation consisted of an integrative literature review of a quali-quantitative nature, using Bardin's analysis and classification by levels of evidence, whose data collection was carried out via virtual platforms, totaling 26 articles from PubMed and the Biblioteca Virtual em Saúde. From the analysis of the material, it was possible to perceive the multifactorial nature of the individual's interaction with the Place, which is composed of several dimensions of human relational existence, as well as understanding that space constructs the individual and at the same time is constructed by him all days.